Development of Dendrobium officinale pulpy drink - Asjad, Muhammad Arsalan; Lou, Zaixiang; Mukesh, Mukesh; Anwar, Sehar; Munam, Hafiz Abdul; Hassan, Farazia; Al-Ansi, Waleed (International Journal of Environment, Agriculture and Biotechnology, 2023)
D. officinale is a renowned botanical species in China with a rich historical background associated with its extensive use in traditional medicine. This research aims to develop a pulpy drink using the Stem of the D. officinale plant and enhance its thermal stability. In order to enhance the thermal stability of the beverage, multiple amounts of xanthan gum were used in the formulation. The physical stability of the D. officinale pulpy drink was assessed by measuring particle size, Zeta potential, particle sedimentation, viscosity, and color. The current research findings indicated that the beverage with a composition of 3% D. officinale pulp and 0.4% xanthan gum exhibited the highest level of physical stability. This beverage exhibited the smallest particle size, negative zeta potential, viscosity, and no sedimentation.